Mal: instrument rating paretic upper member - Diz, Elisabete (2014)
Stroke is one of the main causes of mortality and morbidity worldwide. In the specific case of Portugal,stroke is still the leading cause of death, being responsible for the high rate of disability and functional dependence of the adult population.